The Relationships between Mobile Environment Cues towards Mobile Purchasing Intention and Spreading Positive User – Generated Content: A Pilot Study - Azlin Zanariah Bahtar; Mazzini Muda; Noraznira Abd. Razak (International Journal of Supply Chain Management, 2018)
Evolution of technology indirectly has impacted customer purchasing behaviour and sellers promotional activity. Generally, before customers have a purchase intention, they will seek for information and all the information usually can be obtained online especially on social media. Rationally, customers would believe words generated by others who have consumption experiences as it is seen to be more credible and trustworthy. Words provided by others on online is known as User-Generated Content. Allowing buyers to fully rely on words generated by others may not always be favourable to online sellers. Therefore, researchers conducted this pilot study with only 30 respondents to determine the relationship between Mobile Environment Cues towards Mobile Purchase Intention and Spreading Positive User-Generated Content with Shaped Discussion as one of the cues. SPSS was used and correlation analysis and multiple regression analysis were employed. Out of 5 hypotheses, 3 were supported and 2 were not. Finding also revealed that information provided by sellers does have weak relationship with mobile purchase intention.